Rate of Primary Cesarean Delivery by Language Preference among Nulliparas - Comfort, Lizelle; Jain, Meaghan; Wu, Haotian; Nathan, Lisa (American Journal of Perinatology, 2023)
Objective Sociodemographic factors such as race/ethnicity and socioeconomic status affect primary cesarean delivery rates. Language is associated with disparate health care outcomes but has not been well studied in obstetrics. We examined the association between primary unscheduled cesarean delivery rate and preferred patient language.Study Design A retrospective cohort study was conducted at an urban medical center between January 2017 and January 2020. Nulliparous women with early or full-term gestation and having no obstetric or medical contraindication to vaginal delivery were included. We used multivariable linear and logistic regressions to evaluate language differences in cesarean delivery odds and indication for cesarean.Results Of the 1,314 eligible women, 76.8% of patients preferred English, 17.8% Spanish, and 5.4% other languages. Overall cesarean delivery rate was 27.6%. Controlling for age, race/ethnicity, body mass index, insurance, gravidity, pregnancy comorbidities, labor induction, and infant birth weight, Spanish- and other language-speaking women had significantly higher odds of undergoing cesarean compared with English-speaking women (adjusted odds ratio [OR]: 1.75; 95% confidence interval [CI]: 1.25, 2.46). Relative proportions of indications for cesarean did not differ by language group. Documented interpreter use was an effect modifier on the relationship between language preference and cesarean (OR with interpreter use: 2.89, 95% CI: 1.90, 4.39).Conclusion Primary cesarean delivery rates were significantly higher among nulliparous women who prefer languages other than English. This difference may reflect lack of communication, provider bias or discrimination, or other factors, and should be further studied. Interpreter services should be routinely utilized and documented effectively.Key Points
Keywords: patient language; disparities; obstetrics; cesarean delivery; professional interpreter